BUDAYA LENGGER LANANG DALAM FILM KUCUMBU TUBUH INDAHKU KARYA GARIN NUGRAHA DALAM PERSPEKTIF ISLAM - Fajrul Falah; Sayidah Afyatul Masruroh; Anwari; M. Sahrun Ni’am; Ahmad Gunawan Imani (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2021)
Film is considered as a powerful medium of communication to the masses it targets, because of its audio-visual nature, film is an effective medium for conveying a message. But not all messages can be conveyed properly, therefore it is necessary to formulate the problems in this research: what is the Islamic perspective and hadits prespective on lengger lanang culture contained in the film Kucumbu Body Indahku. To answer the formulation of the problem, the researcher uses a qualitative approach, with the method used is Roland Barthes's Semiotics analysis